Vitamin D status by sociodemographic factors and body mass index in Mexican women at reproductive age - Alejandra Contreras-Manzano; Salvador Villalpando; Ricardo Robledo-Pérez (Instituto Nacional de Salud Pública, 2017)
Objective. To describe the prevalence of Vitamin D deficiency (VDD) and insufficiency (VDI), and the main dietary sources of vitamin D (VD) in a probabilistic sample of Mexican women at reproductive age participating in Ensanut 2012, stratified by sociodemographic factors and body mass index (BMI) categories. Materials and methods. Serum concentrations of 25-hydroxyvitamin-D(25-OH-D) were determined using an ELISA technique in 4 162 women participants of Ensanut 2012 and classified as VDD, VDI or optimal VD status. Sociodemographic, anthropometric and dietary data were also collected. The association between VDD/VDI and sociodemographic and anthropometry factors was assessed adjusting for potential confounders through an estimation of a multinomial logistic regression model. Results. The prevalence of VDD was 36.8%, and that of VDI was 49.8%. The mean dietary intake of VD was 2.56 μg/d. The relative risk ratio (RRR) of VDD or VDI was calculated by a multinomial logistic regression model in 4 162 women. The RRR of VDD or VDI were significantly higher in women with overweight (RRR: 1.85 and 1.44, p<0.05), obesity (RRR: 2.94 and 1.93, p<0.001), urban dwelling (RRR:1.68 and 1.31, p<0.06), belonging to the 3rd tertile of income (RRR: 5.32 and 2.22, p<0.001), or of indigenous ethnicity (RRR: 2.86 and 1.70, p<0.05), respectively. Conclusion. The high prevalence of VDD/VDI in Mexican women calls for stronger actions from the health authorities, strengthtening the actual policy of food supplementation and recommending a reasonable amount of sun exposure.